Rummaging on a Research Method - Pandey, Shiva Ram (Journal of NELTA Koshi (JoNK), 2024)
Rummaging on a research method is a review article on qualitative research method. It briefly presents what qualitative research is, its philosophical perspectives, paradigms and parameters, nature and features, how to generate qualitative data and analyze them, rigour and quality in qualitative research. It draws the conclusion that qualitative research is really good in the field of social and educational research to develop quality in teaching, learning and research. Furthermore, it was explored from the study that qualitative research method is subjective in nature. It uncovers and discovers rich data and reality in a naturalistic context. It is both reflexive and communicative. It has its deep faith on multiple realities. It is highly rigorous in terms of process to unearth in-depth information out of a phenomenon. It aspires to make a quest for maintaining quality in the field of research.